Improving performance of store management: a case study of Dhaka Electric Supply Company Ltd. (DESCO) - Morshed, Rashed (BRAC University, 2014)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2011.